Headache in Vale do Taquari: a retrospective study - Souza, Jesuély Spieckert de; Ribeiro, Mariana Cristina; Gomes, Paula Schmitz; Palmeira, André Luiz; Friedrich, Frederico; Grassi, Vanise (Headache Medicine, 2025)
IntroductionPrimary headaches are highly prevalent neurological disorders and represent a global public health issue, with a significant impact on functionality and quality of life. Despite this, studies indicate that a considerable portion of sufferers, especially those with migraine, remain without a formal diagnosis, which hinders adequate clinical management. In this context, understanding the epidemiological profile at regional levels is essential.ObjectiveTherefore, the aim of this study is to describe the profile of patients presenting with headache complaints at a specialized neurology center in Vale do Taquari (Lajeado/RS), to support healthcare strategies for this population.MethodsObservational, descriptive, and retrospective study based on the review of medical records from a specialized clinical center in Vale do Taquari, Rio Grande do Sul. Patients aged 18 years or older, attended for primary headache complaints between August 2017 and February 2024 were included. Sociodemographic, clinical (ICHD-3 diagnosis), and treatment variables were collected and analyzed using descriptive statistics. The project was approved by the Research Ethics Committee.ResultsThe sample consisted of 111 patients, with a mean age of 48 years and a predominance of females (n=91, 82%). Most self-identified as white (n=96, 87%), and (n=18, 35%) had a low level of education (5 to 8 years). The most prevalent diagnosis was migraine without aura (n=54, 48.6%), followed by cervicogenic headache (n=22, 19.8%) and tension-type headache (n=17, 15.3%). Neurological examination abnormalities were detected in some patients, mainly in cranial nerves and sensory function. Magnetic resonance imaging was the most requested imaging exam (n=51, 45.9%). Acute treatment was predominantly monotherapy, with common analgesics being the most prescribed. Prophylaxis was instituted in 74 (66.4%) of cases, mainly with tricyclic antidepressants and beta-blockers.ConclusionThis study allowed the characterization of the clinical and sociodemographic profiles of patients presenting with headache complaints at a specialized center in Vale do Taquari, highlighting a predominance of females, a mean age of 48 years, and a higher prevalence of migraine without aura. A high rate of imaging requests was observed, not always aligned with guidelines, as well as predominant use of common analgesics for acute treatment and tricyclic antidepressants and beta-blockers for prophylaxis.